2020
DOI: 10.5539/jel.v10n1p47
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Students’ Mathematics Anxiety Levels and Mathematics Performances at the Foundation Level

Abstract: For many students, mathematics is regarded as a challenging subject to learn and master in class. One of the significant factors contributing to the students’ difficulties in learning mathematics is caused by a phenomenon called mathematics anxiety. Mathematics anxiety is a feeling of unease and anxiety toward mathematics and it can be different from person-to-person. Understanding the effects of mathematics anxiety levels on students’ mathematics performances in class can be the key to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…The study conducted by Siaw et al (2021) in Malaysia showed that there is "a weak positive correlation between students' anxiety levels and their mathematics performance" (p. 47). The students' behaviour regarding the process of learning math was analysed through a questionnaire.…”
Section: Oginni Et Al (2021) In Their Article Effects Of Mastery Lear...mentioning
confidence: 99%
“…The study conducted by Siaw et al (2021) in Malaysia showed that there is "a weak positive correlation between students' anxiety levels and their mathematics performance" (p. 47). The students' behaviour regarding the process of learning math was analysed through a questionnaire.…”
Section: Oginni Et Al (2021) In Their Article Effects Of Mastery Lear...mentioning
confidence: 99%
“…Berbagai penelitian terkait kecemasan matematika dengan tujuan yang beragam telah dilakukan mengingat dampak yang ditimbulkan oleh hal ini. Penelitian dengan tujuan untuk menginvestigasi hubungan antara kecemasan matematika mahasiswa terhadap performa mereka, level kecemasan mahasiswa berdasarkan program studi, dan mengetahui perilaku mahasiswa terhadap matematika (Siaw et al, 2020). Penelitian dengan tujuan untuk mengetahui dampak kecemasan matematika berdasarkan pada perbedaan gender (Sonia et al, 2020).…”
Section: Pendahuluanunclassified
“…Mathematics, among other things, aids in the comprehension and mastery of other subjects in the Sciences and arts. When it comes to teaching children math, educators must be aware of the obstacles they will face, as it is common for children to have unfavorable attitudes toward math when they are younger [7].…”
Section: Introductionmentioning
confidence: 99%